Socio-demographic Characteristics of Newly Reported HIV Cases in Iraq (1986-2019) - Jalil Ibrahim Saleh; Nawar Sahib Khalil; Haitham Noaman Al-Koubaisy; Hussien Ali Mahdi; Hadeer Naeem; Najoh Kadhim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: HIV/AIDS is considered as one of the most important public health concern faced by manydeveloped and developing countries.Objective: To study the basic socio-demographic characteristics of the newly reported HIV Iraqi casesduring the period extending from 1986 to 2019.Subjects and Methods: This is across sectional study conducted using data from newly reported HIVIraqi cases from March 2018 to March 2020. These data were available from the patient’s records at theIraqi National HIV/AIDS Program Centre. Annual registration statistics covering the period from 1986 to2019 were reviewed. The diagnosis was done through identification of anti-HIV antibodies using primarilyELISA as screening test and positive cases were confirmed by Western blot assay. The obtained data werecategorized according to the socio-demographic variables and were analyzed statistically.Results: A total number of newly reported HIV Iraqi cases covering the period from 1986 to 2019 was 892cases. The majority of the cases were males (83%), from 21-39 years old (60.3%), alive (65.7%), and single(53.4%). Most of them were from low educational level (45.1%), low socio-economic status (48.3%), andliving in urban areas (75.6%) from Central origin (63.2%).Conclusions: Identification of these findings may provide important directions for targeting certain sociodemographiccharacteristics of the HIV infections to provide specific support for accessing healthcareservices and evaluating the effectiveness of prevention and control measures.